Gas transport at dense phase conditions for the development of deepwater fields in the Colombian Caribbean sea - Cabarcas Simancas, Manuel; Rada Santiago, Angélica María; Vargas Vera, Brandon Humberto (CT&F - Ciencia, Tecnología y Futuro, 2020)
The purpose of this article is to set out the benefits of using the dense phase gas transport in future projects in the Caribbean Sea and to verify that when operating pipelines at high pressures, more mass per unit of volume is transported, and liquid formation risks are mitigated in hostile environments and low temperatures. This study contains key data about gas production fields in deep and ultra-deep waters around the world, which serve as a basis for research and provide characteristics for each development to be contrasted with the subsea architecture proposed in this paper. Additionally, analogies are established between the target field (Gorgón-1, Kronos-1 and Purple Angel-1) and other offshore gas fields that have similar reservoir properties. Using geographic information systems, the layout of a gas pipeline and a subsea field architecture that starts in the new gas province is proposed. Finally, using a hydraulic simulation tool, the gas transport performance in dense phase is analyzed and compared with the conventional way of transporting gas by underwater pipelines, achieving up to 20 % in cost savings when dense phase is applied.